PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELI KONSUMEN EMKA GENTENG BETON DI CIANJUR - Alifia Nurul Aulia; Hendar Rubedo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the influence of product, promotion, price, and place on purchasing decisions at EMKA Genteng Cianjur. This study is a correlational study using a survey method with a questionnaire instrument. Based on the results of the study, the promotion coefficient r count = .768 with r table (0.05) (15) = 0.657. Thus, it can be concluded that the promotion variable has a significant influence of 51.6% on purchasing decisions at EMKA Genteng Cianjur. Based on the results of the study, the price coefficient r count = 0.768 > r table (0.05) (18) = 0.657. Thus, it is concluded that the price variable has a significant influence of 51.6% on purchasing decisions at EMKA Genteng Cianjur. Based on the results of the study, the purchasing decision coefficient r count = 0.768 > r table (0.05) (18) = 0.657. Thus, it is concluded that the place variable has a significant influence of 51.6% on purchasing decisions at EMKA Genteng Cianjur”, meaning the coefficient is significant. Thus, the hypothesis that states “promotion and price analysis have an influence on purchasing decisions” can be accepted.